Implementation and Effectiveness of Gender-Responsive Occupational Health and Safety for Female Workers in Waste Processing Industries: A Systematic Review - Hutabarat, Dewi Sartika; Ginting, Siska Suci Triana; Zebua, Audry Marselina; salmah, umi; Rochadi, kintoko; Silaban, Gerry; Mardiana, Arfah (Chakra Brahmanda Lentera Institute, 2026)
Background: Female workers in waste processing industries are highly vulnerable to occupational hazards, including biological, chemical, ergonomic, and reproductive risks. Despite the implementation of Occupational Health and Safety (OHS) programs, evidence regarding gender-responsive OHS practices for female workers remains limited, particularly in low- and middle-income countries (LMICs). This systematic review aimed to synthesise evidence on the implementation and effectiveness of gender-responsive Occupational Health and Safety (OHS) programs among female workers in waste processing industries Methods: A systematic review was conducted following the PRISMA 2020 guidelines. Literature searches were performed in Scopus, PubMed, ScienceDirect, Web of Science, and CINAHL for studies published between 2014 and 2024. Two independent reviewers conducted study screening through title, abstract, and full-text assessment. Methodological quality was evaluated using the Joanna Briggs Institute (JBI) critical appraisal tool. Eighteen studies met the eligibility criteria. Due to heterogeneity in study designs, outcomes, and measurement indicators, meta-analysis was not feasible; therefore, the data were synthesised using a thematic narrative analysis. Results: The PRISMA process identified 1,246 records, of which 18 studies were included in the final synthesis. Studies were predominantly conducted in LMIC settings and involved cross-sectional, qualitative, and mixed-method designs. Three major themes emerged: (1) occupational hazard exposure among female waste workers, (2) implementation of OHS interventions and personal protective equipment (PPE), and (3) barriers to gender-responsive occupational health protection. Most studies reported inadequate PPE utilisation, limited reproductive health protection, and weak institutional OHS policies. The quality of evidence ranged from low to moderate due to methodological heterogeneity and limited longitudinal studies. Conclusion: Gender-responsive OHS implementation in waste processing industries remains suboptimal, particularly in LMICs. Strengthening workplace policies, reproductive health protection, PPE compliance, and gender-sensitive occupational programs is essential to improve worker safety. Future studies should employ longitudinal and intervention-based designs to evaluate the effectiveness of OHS programs among female workers.